Characterization of Two Transposable Elements and an Ultra-Conserved Element Isolated in the Genome of Zootoca vivipara (Squamata, Lacertidae) - Marcello Mezzasalma; Teresa Capriglione; Larissa Kupriyanova; Gaetano Odierna; Maria Michela Pallotta; Agnese Petraccioli; Orfeo Picariello; Fabio M. Guarino (Life, 2023)
Transposable elements (TEs) constitute a considerable fraction of eukaryote genomes representing a major source of genetic variability. We describe two DNA sequences isolated in the lizard Zootoca vivipara, here named Zv516 and Zv817. Both sequences are single-copy nuclear sequences, including a truncation of two transposable elements (TEs), SINE Squam1 in Zv516 and a Tc1/Mariner-like DNA transposon in Zv817. FISH analyses with Zv516 showed the occurrence of interspersed signals of the SINE Squam1 sequence on all chromosomes of Z. vivipara and quantitative dot blot indicated that this TE is present with about 4700 copies in the Z. vivipara genome. FISH and dot blot with Zv817 did not produce clear hybridization signals. Bioinformatic analysis showed the presence of active SINE Squam 1 copies in the genome of different lacertids, in different mRNAs, and intronic and coding regions of various genes. The Tc1/Mariner-like DNA transposon occurs in all reptiles, excluding Sphenodon and Archosauria. Zv817 includes a trait of 284 bp, representing an amniote ultra-conserved element (UCE). Using amniote UCE homologous sequences from available whole genome sequences of major amniote taxonomic groups, we performed a phylogenetic analysis which retrieved Prototheria as the sister group of Metatheria and Eutheria. Within diapsids, Testudines are the sister group to Aves + Crocodylia (Archosauria), and Sphenodon is the sister group to Squamata. Furthermore, large trait regions flanking the UCE are conserved at family level.